1982
DOI: 10.1007/bf01276578
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting effects of 5-hydroxytryptamine on the release of dopamine and acetylcholine in the nucleus accumbens of rat

Abstract: SummaryThe interaction between 5-hydroxytryptamine (5-HT) and the release of dopamine and acetylcholine in the nucleus accumbens of rat was investigated. 5-HT (20/~M) significantly decreased levels of [3H]-dopamine synthesized from [3H]-tyrosine. 5-HT also enhanced the release of [~4C]-dopamine at all concentrations of K + tested (up to 34 raM). The maximal effect of 5-HT occurred at 15 mM K + and was reversed by methysergide (3/zM). Increasing concentrations of Ca 2+ facilitated the releasing effect of 5-HT u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
1

Year Published

1983
1983
1999
1999

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 30 publications
1
8
1
Order By: Relevance
“…However, the effect is evident only at high doses of 5-HT (1OOumoll-) and is not changed even by a reuptake inhibitor such as paroxetine (Table 1). This pattern of action differs from that reported by other authors (De Belleroche & Gardiner, 1982;Gillet et al, 1985) who demonstrated that 5-HT even at low concentrations of 1-lOymol 1-1, inhibited tritium efflux induced by potassium (25 mmol -1) in rat brain slices. The different animal species (guinea-pig versus rat) and the different kind of stimulation (electrical stimulation vs KCl depolarization) are probably responsible for this discrepancy.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…However, the effect is evident only at high doses of 5-HT (1OOumoll-) and is not changed even by a reuptake inhibitor such as paroxetine (Table 1). This pattern of action differs from that reported by other authors (De Belleroche & Gardiner, 1982;Gillet et al, 1985) who demonstrated that 5-HT even at low concentrations of 1-lOymol 1-1, inhibited tritium efflux induced by potassium (25 mmol -1) in rat brain slices. The different animal species (guinea-pig versus rat) and the different kind of stimulation (electrical stimulation vs KCl depolarization) are probably responsible for this discrepancy.…”
Section: Discussioncontrasting
confidence: 99%
“…In fact, in the whole animal, 5-HT or 5-HT-mimetic drugs increase acetylcholine (ACh) content in different brain areas (Envrard et al, 1977;Samanin et al, 1978;Consolo et al, 1980), probably by inhibiting cholinergic neurone activity. Accordingly, 5-HT and 5-HTreleasing drugs reduce the ACh efflux from rat nucleus accumbens slices (De Belleroche & Gardiner, 1982) and from rat hippocampal synaptosomes (Maura & Raiteri, 1986).…”
Section: Introductionmentioning
confidence: 95%
“…Evidence from many sources indicates that serotonergic input directly modulates nucleus accumbens and striatal neurons, but the level at which this interaction occurs is controversial. Studies on the release of DA have suggested that serotonin affects DA terminals in the nucleus accumbens and striatum (9)(10)(11)(12). In contrast, biochemical and behavioural studies have indicated that the effect of serotonin is post-synaptic to dopaminergic neurons in both the nucleus accumbens and striatum (13)(14)(15)(16).…”
Section: Introductionmentioning
confidence: 94%
“…For example, there is evidence that serotonin may inhibit (de Belleroche and Bradford 1980;Ennis et al 1981;Westfall and Tittermary 1982;Blandina et al 1988) as well as stimulate DA release in the striatum (Benloucif et al 1993;West and Galloway 1996;De Deurwaerdere et al 1997). Similarly, local application of 5-HT or 5-HT agonists have been shown to reduce (de Belleroche and Gardiner 1982) and facilitate dopamine efflux in the nucleus accumbens (Guan and McBride 1989;Parson and Justice 1993). In respect to the 5-HT 2 receptor agonist properties of psilocybin, it is of particular note that 3,4-methylenedioxymethamphetamine (MDMA), a potent 5-HT releasing agent, has been shown to increase impulse-mediated striatal dopamine release through 5-HT 2 receptor activation (Schmidt et al 1992;Palfreyman et al 1993;Schmidt et al 1994;Yamamoto et al 1995;Gudelsky and Nash 1996).…”
Section: The Modulating Effects Of Serotonin On Dopamine Neurotransmimentioning
confidence: 99%